Determination of Lead Pollutants in Acid Batteries and Liquid Gases in Aleppo-Syrian Company Using Total Suspended Particulate and Chemical Trap Methods - Aziz Ramadan, Abdul; Mandil, Hasna; Hasan Ismail, Mahmoud (Asian Journal of Chemistry, 2010)
Environmental and biological monitoring of lead in acid batteries and liquid gases in Aleppo-Syrian company using total suspended particulates of aerodynamics particle sizes larger 0.3 μm and chemical trap for total lead in air were studied. The lead contents in working atmosphere with total suspended particulates and chemical trap and in the blood of workers employed in different sections were measured by atomic absorption spectroscopy. The results showed that high mean of lead concentration in air in all different sections of the factory were more than the recommended maximum by National Ambient Air Quality Standards (NAAQS). The most polluted section is milling oxide with 2365 and 4787 μg/m3, using total suspended particulates and chemical trap, respectively. The level of lead in blood was estimated to be at about 36 % in the employees of different sections (30-94 μg/dL) and it was higher than the values prescribed by American Conference of Governmental Industrial Hygienists (ACGIH).